Neuropathic Pain - Gierthmühlen, Janne; Baron, Ralf (Seminars in Neurology, 2016)
Diagnosing neuropathic pain and distinguishing it from nociceptive pain can be challenging, but is essential because both forms of pain require different treatment strategies. The diagnosis of neuropathic pain is primarily based on clinical findings. Therefore, a careful, focused history and an examination of the signs characteristic of neuropathic pain are crucial. Imaging techniques and electrophysiological examinations, as well as punch skin biopsy can support the clinical diagnosis. Ideally, treatment should be individualized using a mechanism-based approach. However, current treatments are usually dispensed without precision, and calcium-channel-acting modulators (pregabalin, gabapentin), tricyclic antidepressants, and serotonin-noradrenalin reuptake inhibitors (duloxetine, venlafaxine) represent first-line treatment options for neuropathic pain. Although neurostimulation techniques for the treatment of refractory chronic pain have become more important, most evidence of long-term effectiveness and safety is still limited, which strengthens the need for larger randomized controlled trials before final recommendations can be made.
Keywords: neuropathic pain; nociceptive pain; chronic pain; sensory signs and symptoms; treatment